Pembangunan Sistem Informasi Penerimaan Santri Baru (PSB) berbasis Web menggunakan Framework Codeigniter (Studi Kasus: MAS Nurul As'adiyah Callaccu Kota Sengkang) - Nurul Inayah; Imam Cholissodin; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
New Santri Admissions (PSB) or known as New Student Admissions (PPDB) are a series of processes carried out by educational institutions such as schools to select prospective students. The process of admitting new students at MAS Nurul As'adiyah Callacu, Sengkang city has a flow for taking forms, filling out forms, returning forms, registering by administration (determining majors), selecting tests, announcing and introducing the scope of the madrasah, a series of processes still using paper media in the implementation process resulting in several problems. As many as 70% of prospective santri come from outside the region, thus requiring them to visit schools to carry out the registration process. In addition, registration using paper media also causes data accumulation and additional work for the PSB committee to enter data into the excel application. Based on these problems, research on the construction of new santri admissions websites is expected to be a solution. The first process carried out was requirements engineering and designing and producing 6 actors, 70 functional requirements, 2 non-functional requirements and 17 database entities. Then, the system is implemented using the PHP programming language, codeigniter framework with MySQL database. after that it is tested at the unit stage, integration, validation and a compatibility and performance testing process is carried out with the results that the content and system functions can run 100% well.